Effect of different seed coating on seed quality parameter, leaf emergence and dry matter production of tomato (Solanum lycopersicum) - D.P. Singh; Rajiv; Meenakshi Kumari; H.G. Prakash (Annals of Agricultural Research, 2022)
A field experiments was carried out for three years during winter season of 2014-15, 2015-16 and 2016-17 at Chandra Shekhar Azad University of Agriculture and Technology, Kanpur to determine the effect of different seed coating in tomato cv. Azad T-6. The experiment consisted of 6 treatments involving one control viz. T1 : carbendazim @ 2g/kg seed, T2 : imidacloprid @ 2ml/kg seed, T3:diammonium phosphate @ 30g/kg seed, T4: micronutrient mixture @ 20g/kg seed, T5: carbendazine @ 2g/kg seed + imadacloprid @ 2ml/kg seed + micronutrient mixture @ 20g/kg seed and T6 : uncoated that is control. As compared to all other treatment carbendazine @ 2g/kg seed + imadacloprid @ 2ml/kg seed + micronutrient mixture @ 20g/kg seed (T5 ) exhibited highest values for all observations (seed germination (92%), shoot length (5.74 cm), root length (5.22 cm ), seedling length (10.98 cm), DMP (0.102), seedling vigour index-1 (1010.38) and seedling vigour index-II (10.33) except days to leaf emergence, which is best in micronutrient mixture @ 20g/kg seed (T4 ) and diammonium phosphate @ 30g/kg seed (T3 ) respectively followed by treatment T1 carbendazine @ 2g/kg seed (T1 ) whereas lowest values were observed for uncoated control (T6 ).